The Views of Several Indonesian Reformed Theologians Regarding Ecumenicity - Agustinus M.L. Batlajery (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: Based on historical researches concerning ecumenical movement in Indonesia, it could be found that the formation of the Council of Churches in Indonesia (DGI) which later changed its name to the Communion of Churches in Indonesia (PGI) can not be separated from the role of Calvinist or Reformed church leaders and theologians at the time. In discussing about stimulus and urgency for unity among various churches in Indonesia, we can see that the views of several Reformed figures was very significant. Their opinions were effected by Calvinist thinking that chracterized their churches. This article is trying to describe the views of several Indonesian Reformed theologians before and after the formation of DGI/PGI regarding ecumenicity. Therefore we can say that Calvinist thinking has played very valuable role in the ecumenical movement in Indonesia.Â KEYWORDS:Â ecumenicity, ecumenical movement, church unity, Indonesian Reformed Theologians, Calvinist thinking.